Evolutionary Transition of GAL Regulatory Circuit from Generalist to Specialist Function in Ascomycetes. Issue 8 (August 2018) - Choudhury, Baharul I.; Whiteway, Malcolm
Abstract : The Gal4 transcription factor (TF) controls gene expression by binding the DNA sequence motif CGG(N11 )CCG. Well studied versions regulate metabolism of glucose in Candida albicans and galactose in Saccharomyces cerevisiae . Gal4 is also found within Aspergillus species and shows a wide range of potential binding targets. Members of the CTG clade that reassigned CUG codons from leucine to serine lack the Gal80 binding domain of Gal4, and they use the TF to regulate only glycolytic genes. In this clade, the galactose catabolic pathway (also known as the Leloir pathway) genes are regulated by Rtg1/Rtg3. In the WGD species, the complete Gal4/Gal80 module is limited to regulation of the Leloir pathway, while glycolysis is controlled by Gcr1/Gcr2. This shows a switch of Gal4 from a generalist to a specialist within the ascomycetes, and the split of glucose and galactose metabolism into distinct regulatory circuits. Highlights: Gal4 is a key regulatory protein in fungal metabolism, and its potential ortholog is present across the ascomycetes (except Taphrinomycotina). A truncated Gal4 protein is present only in the CTG clade (CTG clade reassigned CUG codons from leucine to serine). Though the cysteine-rich N terminus region, which is crucial for DNA recognition, is present in all the species in which Gal4 is present, the C-terminal domains that interact with Gal80 are missing in the CTG clade and their ancestor groups. Our findings suggest a generalist function for Gal4 in the ancestral lineage that subsequently specialized into regulation of glycolytic pathway genes in the CTG clade and Leloir pathway genes in recently evolved species.